THE COLLABORATIVE BUSINESS INCUBATION MODEL AND ITS IMPACT ON CREATIVE INDUSTRIES INNOVATION IN EAST JAVA, INDONESIA - Anjaningrum, Widiya Dewi; Sidi, Agus Purnomo; Yogatama, Ahmad Nizar; Hermawati, Adya; Suci, Rahayu Puji (LP2M Institut Teknologi dan Bisnis Asia Malang, 2023)
Creative industries must innovate in this digital era to face the rapidly changing business environment and fierce competition. This study explored the collaborative business incubation model by stakeholders in the creative economy sector and its impact on tenant innovation. The innovations emphasized in this study are product innovation and marketing innovation. A total of 190 creative entrepreneurs in East Java have been researched using a set of questionnaires and produced quantitative data, which is then analyzed statistically through PLS analysis. The study results show that business incubation mentors significantly affect product innovation, not marketing innovation. On the other hand, the business incubation method significantly affects marketing innovation but not product innovation. Meanwhile, the business incubation curriculum significantly affects both product and marketing innovation. Further research is expected to analyze the type of mentor and the right business incubation method for tenants to significantly impact product and marketing innovation.